Reconciling before educating?: Narratives of conflict and peace among teachers in Côte d’Ivoire - Kuppens, Line; Langer, Arnim (International journal of intercultural relations, 2020)
While teachers are generally perceived as positive agents of change in post-conflict countries, recently researchers have started questioning teachers’ ability and willingness to teach ‘peace’ after conflict. The vast majority of these studies have been qualitative in nature. The current paper makes an important contribution to this debate by analysing quantitatively how teachers’ narratives of the violent past affect their teaching practices in Côte d’Ivoire, a country that emerged from violent conflict in 2011. Drawing on a survey conducted among secondary school teachers (n = 984) in Abidjan, we show that teachers remain sharply divided along ethno-political lines concerning their perceptions of the past conflict and current peace and reconciliation process. There also exists a potentially problematic relation between these narratives and teachers’ teaching practices: Teachers in support of the narrative associated with the current government seem much more willing to discuss their country’s violent past in the classroom than others.
Gesehen am 28.05.2020